Development of a journal club on the Nursing management process - Viviana Carolina Oyan de Moraes; Wilza Carla Spiri
ABSTRACT Objective: To develop a journal club on management topics in Nursing. Method: Action research, adopting content analysis as methodological reference and the journal club strategy. 12 nursing managers of a public hospital in the state of São Paulo participated from August to November 2016. Results: data showed the participation of nurses in the journal club in five meetings planned collectively with the following topics: "aspects regarding organization", with the subtopics "planning", "work process", "structure" and "people management"; and the topic "aspects regarding the team", with the subtopics "autonomy", "behavior/attitude", "awareness" and "social problems". Conclusion: The study showed the comprehensiveness of topics the journal club can address regarding management, and how scientific basis is important in the daily life of nursing managers to improve quality of care and the ability to manage.